OP0046 Decreased Circulating ILC2 Levels Correlate with Skin Fibrosis in Human Systemic Sclerosis and Are Associated with A Skewing of The ILC1/ILC2 Balance in The Skin. (15th July 2016) - Laurent, P.; Manicki, P.; Douchet, I.; Lazaro, E.; Duffau, P.; Richez, C.; Séneschal, J.; Constans, J.; Pradeu, T.; Blanco, P.; Contin-Bordes, C.; Truchetet, M.-E.
Abstract : Background: Interleukin (IL)13 is considered as a key downstream mediator in the development of Systemic sclerosis (SSc) fibrosis 1 . The recently described type 2 innate lymphoid cells (ILC) produce higher amounts of IL13 than Th2 cells under certain stimulatory conditions 2 . Our recent work show that endothelial cells are an important source of thymic stromal lymphopoietin (TSLP) in SSc 3, which is an inducer of IL13 production by ILC2. Altogether, we assume that ILC2 could have a role in the promotion of SSc fibrosis. Objectives: To analyse ILC populations in whole blood and skin of SSc patients and heatlhy donors (HD) and to correlate to clinical parameters. Methods: 25 SSc and 15 HD were prospectively enrolled between September 2015 and January 2016 in the University Hospital of Bordeaux. Skin biopsies were performed in fibrotic skin for 2 SSc patients and in pieces of brachioplasty for HD. All patients signed informed consent. Analysis were done on fresh blood after Red Blood lysis and on cells from skin biopsies digested with liberase and DNase. ILC were measured by flow cytometry using Beckman Coulter and Miltenyi Biotech kits respectively. For peripheral blood and skin, results are expressed as median and means respectively. Mann-Whitney test is used for comparisons. Results: In SSc patients, circulating ILC were significantly decreased both in frequency (0.0094% of total cells [0.0005–0.052] in HD vs. 0.0024% [0.0002–0.029] in SSc, p=0.006) and in absolute counts (0.146 [0.0089–1.641] in HD vs. 0.032 [0.0049–0.427] in SSc, p=0.0005). This global decrease was mainly due to the decrease of the ILC2 frequency (0.0077% of total cells [0.0009–0.031] in HD vs. 0.0024% [0.00–0.01] in SSc, p=0.0009) and absolute counts (0.123 [0.0153–0.574] in HD vs. 0.033% [0.00–0.167] in SSc, p<0.0001). The number of ILC2 in peripheral blood was inversely correlated to skin fibrosis as assessed by the modified Rodnan skin score (r=-0.6, p=0.0041, using a Pearson test). Analysis of ILC content in total cells showed that ILC2 are present in both normal and SSc skin. However, we showed a skewing towards ILC2 (83.6% of total ILC in SSc vs. 66.4% in HD) at the expense of ILC1 (7.5% in SSc vs. 18.85% in HD) in SSc skin, while ILC3 were not affected. Conclusions: SSc patients are characterized by a decrease of the ILC2 subpopulation in peripheral blood inversely correlated to skin fibrosis and a skewing of the type 1/type 2 ILC balance in the skin towards ILC2. Altogether these results show for the first time flow cytometry analysis of ILC content in whole blood and skin of SSc patients, which pave the road for further extensive phenotypic analysis. References: Fichtner-Feigl S, et al. Nat Med 2006;12:99–106. Hazenberg MD, Spits H. Blood 2014;124:700–709. Truchetet ME, et al. In revision in Arthritis Rheum Disclosure of Interest: None declared